Semantics of Program Representation Graphs - Ramalingam, G.; Reps, Thomas (1989)
Program representation graphs are a recently introduced intermediate representation form for programs. In this paper, we develop a mathematics semantics for the graphs by interpretating them as data-flow graphs. We also study the relation between this semantics and the standard operational semantics of programs.